2020
DOI: 10.1136/bcr-2019-231080
|View full text |Cite
|
Sign up to set email alerts
|

Retrorectal cyst: proteus in the backyard—case series and literature review

Abstract: Retrorectal cysts are cystic lesions located in the retrorectal space and are a distinct subset of retrorectal tumours, which are often misdiagnosed due to their rarity and mimicry of symptoms caused by common diseases. We have described the presentation and management of four patients who were diagnosed with retrorectal cysts from a 10-year retrospective chart review at our institute, a tertiary care centre. In middle-aged women, the following should raise suspicion of retrorectal cyst: gastrointestinal or ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…A similar female preponderance was reported in the literature for retrorectal cysts and tumors. In a similar case series study, Ramalingam et al observed 4 patients with retrorectal cysts and found out that all of the patients were female (1). In the present study, patients visited the hospital with chief complaints of abdominal pain, pelvic pain, or anal pain.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…A similar female preponderance was reported in the literature for retrorectal cysts and tumors. In a similar case series study, Ramalingam et al observed 4 patients with retrorectal cysts and found out that all of the patients were female (1). In the present study, patients visited the hospital with chief complaints of abdominal pain, pelvic pain, or anal pain.…”
Section: Discussionsupporting
confidence: 50%
“…Histologically, these cysts can be lined by squamous, columnar, cuboidal, or transitional epithelium because they arise from the endoderm of the primitive gut. Two layers of muscles with myenteric nerve plexus can also be in the cyst's wall (1). Considering the anatomical location of duplication cysts, they may cause bowel obstruction, intussusception, volvulus or hemorrhage, or perforation because of gastric mucosa contents inside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation